A preparation method of lignin colorful carbon nanodots and its products and uses
By heating and stirring lignin and 2,4-diaminobenzenesulfonic acid in water in water with a water bath, followed by hydrothermal reaction and extraction steps, blue, green and red multicolor carbon nanodots were successfully prepared, and the degradation efficiency of antibiotics in water was improved by carbon nanodot composite indium zinc sulfide photocatalyst, which solved the problem of insufficient feasibility of controlling colorful fluorescent carbon dots in the prior art, and realized the application of multifunctional water treatment.
Patent Information
- Application Number
- CN202311244422.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-09-26
AI Technical Summary
The feasibility of regulating colorful fluorescent carbon dots in the prior art is insufficient, especially lignin carbon dots are mainly concentrated in blue fluorescence emission, which limits the large-scale preparation of lignin in the field of colorful carbon dots and the actual multifunctional water treatment application.
By heating and stirring lignin and 2,4-diaminobenzenesulfonic acid in water in water with a water bath, followed by hydrothermal reaction and extraction steps, blue, green and red multicolor carbon nanodots were successfully prepared, and the degradation efficiency of antibiotics in water was improved by carbon nanodot composite indium sulfide photocatalyst.
The multi-color control of lignin colored carbon nanodots is realized, its electron transfer characteristics and sensing characteristics are improved, the photocatalytic activity of ZnIn2S4 is effectively enhanced, and the degradation efficiency of antibiotics is improved in water treatment.
Smart Images

Figure CN117327486B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomass nanomaterials and water treatment, and more specifically, to a method for preparing lignin colorful carbon nanodots and water treatment application thereof. Background Art
[0002] Lignin is an aromatic natural polymer compound second only to cellulose in nature. It is not only widely available, non-toxic and inexpensive, but also has a rich aromatic structure and a high carbon content, making it an ideal carbon source for preparing carbon dots. However, today, as a by-product, industrial lignin is produced on a large scale by papermaking and biorefining plants, with an annual output of about 60 to 70 Mt, most of which is directly incinerated, causing serious environmental pollution and waste of resources.
[0003] In recent years, carbon dots (CDs), as an emerging zero-dimensional fluorescent carbon nanomaterial, have been widely used in bioimaging, sensing, catalysis, and optoelectronics due to their low toxicity, good biocompatibility, low cost, and chemical stability. Among them, carbon dots can improve the visible light response of photocatalytic composite materials and the separation efficiency of photogenerated electron-hole pairs due to their excellent photogenerated electron transfer performance, and have outstanding application potential in the field of catalysis. However, the current dilemma in the study of carbon dots lies in the controllability of their multicolor luminescence. At present, multicolor luminescent carbon dots are synthesized from a variety of different precursors, and the preparation process is complicated and the yield is low, so they cannot be widely used in practice. In particular, the existing research on lignin carbon dots mainly focuses on blue fluorescence emission, which also restricts the large-scale preparation of lignin in the field of colorful carbon dots and the actual multifunctional water treatment application. Summary of the invention
[0004] The problem solved by the present invention is that the feasibility of regulating the colorful fluorescent carbon dots described in the prior art is insufficient, and a method for preparing lignin colorful carbon nanodots is provided, which can obtain blue, green and red multi-color carbon nanodots with excellent electron transfer properties and sensing properties.
[0005] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0006] A method for preparing lignin colorful carbon nanodots comprises the following steps:
[0007] (3) adding lignin and 2,4-diaminobenzenesulfonic acid to water, heating and stirring in a water bath, and then filtering and separating to obtain a filtrate and a filter residue;
[0008] (4) dispersing the filter residue obtained in step (1) in ethanol and performing a hydrothermal reaction; filtering the solution obtained by the hydrothermal reaction to remove insoluble matter, and then performing rotary evaporation and freeze drying to obtain a brown powder;
[0009] (3) adding the brown powder obtained in step (2) into a mixed solvent of water and dichloromethane for extraction to obtain an upper layer of blue fluorescent carbon nanodots (B-CDs) solution and a lower layer of red fluorescent carbon nanodots (R-CDs) solution;
[0010] (4) subjecting the filtrate obtained in step (1) to a hydrothermal reaction, filtering the solution obtained by the hydrothermal reaction to remove insoluble matter, dialyzing it, and then filtering it with an aqueous filter membrane to obtain a green fluorescent lignin carbon nanodot (G-CDs) solution.
[0011] According to the above scheme, in step (1), the mass ratio of lignin to 2,4-diaminobenzenesulfonic acid is 1:(0.5-2), and the volume ratio of the total mass of lignin and 2,4-diaminobenzenesulfonic acid to water is 1g:(40-60)mL (solid-liquid ratio).
[0012] According to the above scheme, in step (1), the water bath heating temperature is 70-90° C., and the heating time is 0.5-2 h; and the filtration is performed by slow or medium speed filter paper filtration.
[0013] According to the above scheme, in step (2), the concentration range of the filter residue in ethanol is 6 to 8 g / L; the hydrothermal reaction temperature is 160 to 220° C., and the reaction time is 6 to 10 h; the rotary evaporation temperature is 50 to 70° C.; the freeze-drying temperature is -45 to -60° C., and the time is 1 to 2 days.
[0014] According to the above scheme, in step (3), the mixed solvent is prepared by mixing water and dichloromethane in a volume ratio of 1:(0.8-1.2); the solid-liquid ratio of the brown powder to the mixed solvent is 1g:(140-200)mL. The upper layer is the solvent water layer; the lower layer is the solvent dichloromethane layer.
[0015] According to the above scheme, in step (4), the hydrothermal reaction temperature is 160-220°C, the reaction time is 6-10h; the dialysis uses a dialysis bag with a molecular weight of 1000-4000 for 24-60h; the pore size of the water filter membrane is 0.20-0.45μm.
[0016] According to the above scheme, the blue fluorescent lignin carbon nanodot (B-CDs) solution, the red fluorescent lignin carbon nanodot (R-CDs) solution, and the green fluorescent lignin carbon nanodot (G-CDs) solution are also filtered and freeze-dried to obtain blue fluorescent lignin carbon nanodot (B-CDs) powder, red fluorescent lignin carbon nanodot (R-CDs) powder, and green fluorescent lignin carbon nanodot (G-CDs) powder, that is, powdered lignin colorful carbon nanodots. Among them, the filtration is to further clarify each lignin carbon nanodot solution, remove the insoluble matter or large particles therein, and then freeze-dry to obtain the corresponding purer lignin carbon nanodot powder. The freeze-drying temperature is -45 to -60°C, and the time is 1 to 2 days.
[0017] The present invention also claims protection for blue fluorescent lignin carbon nanodot (B-CDs) powder or solution, red fluorescent lignin carbon nanodot (R-CDs) powder or solution, and green fluorescent lignin carbon nanodot (G-CDs) powder or solution prepared by the above method.
[0018] On the basis of the above, the present invention provides a carbon nanodot composite indium zinc sulfide photocatalyst, in the process of hydrothermal synthesis preparation of indium zinc sulfide (ZnIn2S4, abbreviated as ZIS), the lignin carbon nanodot powder (CDs, selected from one or two or three of G-CDs, B-CDs, G-CDs) of the present invention is added to prepare a carbon nanodot composite indium zinc sulfide photocatalyst (CDs-ZIS photocatalyst). The specific process is as follows:
[0019] Add ZnCl2, InCl3, and thioacetamide (TAA) to a mixed solvent of water and ethanol to obtain a mixed solution; then add one, two, or three of the lignin carbon nanodot powders of the present invention to the mixed solution, stir and / or ultrasonically mix evenly, transfer to a reactor for hydrothermal reaction, and dry the resulting solid product, which is the CDs-ZIS photocatalyst. Among them, the molar ratio of ZnCl2, InCl3, and TAA is 1:2:4, the solid-liquid ratio of ZnCl2 to the mixed solvent is (20-30) mg: (50-70) mL, and the mass ratio of CDs to ZnCl2 is 1: (25-35); the volume ratio of water to ethanol is 1: (0.8-1.5); the stirring and ultrasonic times are both 0.5-1 h; the hydrothermal temperature is 160-220°C, and the hydrothermal time is 6-10 h.
[0020] The above-mentioned carbon nanodot composite indium zinc sulfide photocatalyst (CDs-ZIS photocatalyst) is used to remove pollutants in antibiotic wastewater, by adding CDs-ZIS photocatalyst to the antibiotic contaminated water body, and degrading the pollutants in the water body under light reaction. Among them, the pollutants in the antibiotic wastewater are one or more of tetracycline hydrochloride, oxytetracycline, doxycycline, ciprofloxacin, etc.
[0021] On the basis of the above technology, the present invention can also provide an application of lignin carbon nanodots in monitoring iron ion pollution in water bodies; the lignin carbon nanodots are blue fluorescent lignin carbon nanodots (B-CDs) or green fluorescent lignin carbon nanodots (G-CDs). The application method is: according to the fluorescence intensity of blue or green fluorescent lignin carbon nanodots decreases with the increase of iron ion concentration and is linearly correlated, a small amount of water to be monitored can be added to the lignin carbon nanodot solution, and the concentration of iron ions in the water body can be obtained according to the change of fluorescence intensity, thereby realizing the degree of iron ion pollution in the water body to be monitored.
[0022] On the basis of the above technology, the present invention can also provide an application of a hydrogel of lignin carbon nanodots for visual monitoring of iron ions in water; the lignin carbon nanodots are blue fluorescent lignin carbon nanodots (B-CDs) or green fluorescent lignin carbon nanodots (G-CDs). The application method is: the nanocellulose prepared by TEMPO oxidation method is placed in a freeze dryer for 1 to 2 days to obtain a hydrogel; then the gel is fully soaked in the lignin carbon nanodot solution and the water body to be monitored in sequence, and then the lignin carbon nanodots are illuminated with light of the excitation wavelength, and the fluorescence intensity is observed. According to the decrease in fluorescence intensity as the iron ion concentration increases, visual sensing monitoring is achieved.
[0023] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects compared with the prior art:
[0024] Firstly, the present invention uses natural lignin as raw material, and obtains multicolor fluorescent carbon nanodots through simple and easy methods such as hydrothermal reaction combined with extraction and filtration, thereby realizing colorful regulation of carbon dots; in particular, the use of 2,4-diaminobenzenesulfonic acid increases the nitrogen and sulfur doping amounts of carbon nanodots, thereby improving the fluorescence quantum yield of the carbon dots.
[0025] Second, the colorful carbon nanodots of lignin described in the present invention can effectively enhance the photocatalytic activity of ZnIn2S4. The residual antibiotics in the water environment are ecotoxic and difficult to degrade. The present invention uses carbon nanodots composite indium zinc sulfide photocatalyst to effectively improve the degradation of residual antibiotics in water, which can be widely promoted and applied in pollution control.
[0026] Third, the colorful lignin carbon nanodots prepared by the present invention have obvious fluorescence sensing properties, especially the blue fluorescent lignin carbon nanodots (B-CDs) or the green fluorescent lignin carbon nanodots (G-CDs) can be used to detect iron ions in water bodies with high selectivity and sensitivity; and can be applied to the visualization detection of hydrogels to realize intelligent fluorescence switching, which can be effectively applied to the fields of environmental monitoring and ion sensing. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] FIG1 is a fluorescence spectrum of lignin colorful carbon nanodots prepared in Example 1 at different excitation wavelengths, and FIGS. ac are B-CDs, G-CDs, and R-CDs, respectively.
[0028] Figure 2 This is the detection response diagram of G-CDs prepared in Example 1 in different metal ion solutions.
[0029] Figure 3 The G-CDs prepared in Example 1 were exposed to 10000 μM Fe 3+ Visualized hydrogel sensing in solution.
[0030] Figure 4 This is a scanning electron microscope (SEM) image of the ZIS and RCDs-ZIS photocatalysts prepared in Application Example 1.
[0031] Figure 5 This is a graph of the degradation activity of the RCDs-ZIS catalyst prepared in Application Example 1 at different tetracycline hydrochloride concentrations. DETAILED DESCRIPTION
[0032] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.
[0033] Example 1
[0034] A method for preparing lignin colorful carbon nanodots, comprising the following steps:
[0035] (1) 1 g of lignin and 1 g of 2,4-diaminobenzenesulfonic acid were added to 100 mL of water, and magnetically stirred in a water bath at 80°C for 1 h, and then filtered through medium-speed filter paper to obtain a filtrate and a filter residue; the filter residue was rinsed with deionized water for 2 to 3 times, and dispersed in 100 mL of ethanol to obtain a filter residue-ethanol solution (the concentration of the filter residue in ethanol was about 7 g / L);
[0036] (2) transferring the filter residue-ethanol solution obtained in step (1) to a reaction kettle, performing a hydrothermal reaction in an oven at 200° C. for 8 h, filtering the solution obtained after hydrothermal reaction to remove large particles, and then performing rotary evaporation at 60° C. and freeze-drying at -55° C. to obtain a brown powder solid;
[0037] (3) transferring the brown powder solid obtained in step (2) to a separatory funnel containing water and dichloromethane in a volume ratio of 1:1 for extraction (the mass of the brown powder is 0.6 g, and the volumes of water and dichloromethane are both 100 mL) to obtain a blue fluorescent carbon nanodot (B-CDs) solution on the upper layer and a red fluorescent carbon nanodot (R-CDs) solution on the lower layer;
[0038] The blue fluorescent carbon nanodot (B-CDs) solution or the red fluorescent carbon nanodot (R-CDs) solution can be further filtered to make it clearer, and then rotary evaporated and freeze-dried to obtain blue fluorescent carbon nanodot (B-CDs) powder or red fluorescent carbon nanodot (R-CDs) powder respectively;
[0039] (4) The filtrate obtained in step (1) was transferred to a reaction kettle and subjected to a hydrothermal reaction in an oven at 200° C. for 8 h. The solution obtained after the hydrothermal reaction was filtered to remove large particles, and then dialyzed with a 3000 molecular weight dialysis bag for 48 h, and then filtered with a 0.22 μm filter head to obtain a green fluorescent carbon nanodot (G-CDs) solution;
[0040] The green fluorescent carbon nanodot (G-CDs) solution can be further filtered to make it clearer, and then rotary evaporated and freeze-dried to obtain green fluorescent carbon nanodot (G-CDs) powder;
[0041] (5) The above blue fluorescent carbon nanodots (B-CDs) solution or powder, red fluorescent carbon nanodots (R-CDs) solution or powder, green fluorescent carbon nanodots (G-CDs) solution or powder, namely, lignin colorful carbon nanodots.
[0042] FIG1 is a fluorescence spectrum of lignin colorful carbon nanodots prepared in Example 1 at different excitation wavelengths. Figure 1a It can be seen that the blue fluorescent carbon nanodots prepared by the present invention have significant fluorescent properties under the ultraviolet excitation wavelength of 280-380nm, and emit a relatively stable blue fluorescence of 420nm under the excitation wavelength of 330nm. Figure 1b It can be seen that the green fluorescent carbon nanodots prepared by the present invention have significant fluorescence characteristics under the ultraviolet excitation wavelength of 390-460nm, and emit a relatively stable green fluorescence of 520nm under the excitation wavelength of 440nm. Figure 1c It can be seen that the red fluorescent carbon nanodots prepared in the present invention have significant fluorescent properties under an ultraviolet excitation wavelength of 530-610 nm, and emit a relatively stable red fluorescence of 651 nm under an excitation wavelength of 570 nm.
[0043] Application Example 1
[0044] The preparation method of carbon nanodot composite indium zinc sulfide photocatalyst (CDs-ZIS photocatalyst) takes red fluorescent carbon nanodots as an example, and the prepared photocatalyst is RCDs-ZIS photocatalyst. The specific preparation process is as follows:
[0045] Weigh 27.26 mg ZnCl2, 117.3 mg InCl3 and 60.1 mg TAA, add 60 mL ethanol aqueous solution (V 乙醇 :V 水 =1:1) and magnetically stirred for 30 min, and at the same time, 1 mg of R-CDs powder was weighed and added to the above ethanol aqueous solution, and ultrasonicated for 1 h. Then, it was transferred to a reactor and subjected to hydrothermal reaction in an oven at 180°C for 8 h. After the hydrothermal reaction, it was cooled to room temperature and then centrifuged at 5000 rpm. The precipitate was taken and washed alternately with water and ethanol for three times, and freeze-dried to obtain the RCDs-ZIS photocatalyst.
[0046] Taking ZIS photocatalyst as a control example, the preparation process of ZIS catalyst differs from that of RCDs-ZIS catalyst in that no R-CDs powder needs to be added.
[0047] Figure 4 The following are scanning electron micrographs (SEM) of ZIS photocatalyst and RCDs-ZIS photocatalyst. Figure 4 It can be seen that the introduction of RCDs did not destroy the flower-like structure of ZIS.
[0048] The ZIS and RCDs-ZIS photocatalysts prepared in this application example 1 were subjected to a photocatalytic degradation of tetracycline (TC) test, and the specific process was as follows: a photocatalyst was added to a 20 mg / L TC solution, and the amount of the photocatalyst added therein was 100 mg / L. After stirring for 30 minutes to reach adsorption equilibrium, the system was illuminated (the light source was a xenon lamp with a visible light filter) to conduct a photocatalytic reaction experiment. 3 mL of the reaction solution was taken at the same time, filtered through a 0.22 μm filter head, and the supernatant was taken, and the TC content in the reaction solution at this time was measured using a UV-visible spectrophotometer.
[0049] The results show that after reacting for 60 minutes in a solution with a photocatalyst concentration of 100 mg / L, the RCDs-ZIS photocatalyst degraded TC by 78%. Under the same conditions, the TC degradation rate of ZIS was only 47%, indicating that the lignin colorful carbon nanodots described in the present invention can effectively enhance the photocatalytic activity of ZnIn2S4, and the carbon nanodot composite indium zinc sulfide photocatalyst described in the present invention can effectively improve the degradation of residual antibiotics in water.
[0050] Figure 5 This is the degradation activity diagram of the RCDs-ZIS photocatalyst prepared in Application Example 1 at different tetracycline hydrochloride concentrations. Figure 5 It can be seen that the RCDs-ZIS photocatalyst prepared by the present invention has a degradation efficiency of 85% within 60 minutes when the catalyst concentration is 200 mg / L in a 20 mg / L TC solution, and has a high removal rate.
[0051] Application Example 2
[0052] Taking green fluorescent lignin carbon nanodots (G-CDs) as an example, they are used to detect heavy metal ion pollution in water. The application method is as follows: take 2.7 mL of G-CDs solution prepared in Example 1 and 0.3 mL of 10000 μM metal ion solution (the metal ion solutions are Co 2+ , Hg 2+ , Fe 3+ 、Zn 2+ 、Cd 2+ , Cu 2+ 、Al 3+ A chloride solution or Cr 3+ 、Ag + 、Ni 2+ The nitrate solution of one of the above compounds is mixed and shaken to obtain a mixed solution; then the emission spectra are measured in sequence at an excitation wavelength of 440 nm to obtain the response results of different metal ions.
[0053] Figure 2 Graph showing the detection response of G-CDs prepared in Example 1 in different metal ion solutions. Figure 2 It can be seen that Fe 3+ The G-CDs solution prepared by the present invention has a good fluorescence quenching effect, and the green fluorescent carbon dot solution can be used to detect whether the polluted water contains metal iron ions.
[0054] Application Example 3
[0055] Taking green fluorescent lignin carbon nanodots (G-CDs) as an example, it is used as a hydrogel visual sensing method to detect heavy metal ion pollution in water. The application method is: the green fluorescent lignin carbon nanodots (G-CDs) solution is used for hydrogel visual sensing, and the specific process is as follows: 5g of nanocellulose prepared by TEMPO oxidation method is weighed in a round mold, and then freeze-dried for 2 days. The obtained hydrogel is soaked in the G-CDs solution prepared in Example 1 and the FeCl3 solution with a concentration of 10000μM for 10 minutes each, and the luminescence phenomenon is observed in a fluorescent light box with an excitation wavelength of 365nm.
[0056] Figure 3 It is the visualized hydrogel sensing of G-CDs in a FeCl3 solution with a concentration of 10000μM, which successfully applies metal ion sensing to visualized detection and realizes the intelligent sensing switch function.
[0057] Example 2
[0058] The difference between this embodiment and embodiment 1 is that the hydrothermal temperature of step (2) and step (4) is 160°C.
[0059] The carbon nanodot solution obtained in step (4) emits 479nm cyan fluorescence at an excitation wavelength of 390nm.
[0060] Application Example 4
[0061] The difference between this application example and application example 1 is that the mass of R-CDs powder is 2 mg, and other conditions are the same.
[0062] The RCDs-ZIS photocatalyst obtained in Application Example 4, under the same experimental conditions as those in Application Example 1, achieved a tetracycline hydrochloride removal rate of 56% in 60 minutes.
[0063] Application Example 5
[0064] The difference between this application example and application example 1 is that the mass of R-CDs powder is 4 mg, and other conditions are the same.
[0065] Under the same experimental conditions as those in Application Example 1, the RCDs-ZIS photocatalyst obtained in Application Example 4 has a tetracycline hydrochloride removal rate of 75% in 60 minutes.
[0066] Application Example 6
[0067] The difference between this application example and application example 1 is that the photocatalyst concentration is 150 mg / L, and other conditions are the same.
[0068] Under the same experimental conditions as in Example 1, the removal rate of tetracycline hydrochloride in Application Example 6 reached 81% in 60 minutes.
[0069] The above embodiments are preferred implementations of the present invention. However, those skilled in the art may make several improvements, modifications and substitutions without departing from the inventive concept of the present invention, which are all within the protection scope of the present invention.
Claims
1. A method for preparing lignin carbon nanodots, characterized in that: The steps include: (1) adding lignin and 2,4-diaminobenzenesulfonic acid to water, heating and stirring in a water bath, and then filtering and separating to obtain a filtrate and a filter residue; wherein the mass ratio of lignin to 2,4-diaminobenzenesulfonic acid is 1:(0.5-2), and the volume ratio of the total mass of lignin and 2,4-diaminobenzenesulfonic acid to water is 1 g:(40-60) mL; (2) dispersing the filter residue obtained in step (1) in ethanol and performing a hydrothermal reaction; filtering the solution obtained by the hydrothermal reaction to remove insoluble matter, and then performing rotary evaporation and freeze drying to obtain a brown powder; wherein the hydrothermal reaction temperature is 160-220° C., the reaction time is 6-10 h; and the concentration range of the filter residue in ethanol is 6-8 g / L; (3) The brown powder obtained in step (2) is added to a mixed solvent of water and dichloromethane for extraction to obtain an upper layer of a blue fluorescent lignin carbon nanodot solution and a lower layer of a red fluorescent lignin carbon nanodot solution; wherein the mixed solvent is formed by mixing water and dichloromethane in a volume ratio of 1:(0.8-1.2); and the solid-liquid ratio of the brown powder to the mixed solvent is 1 g:(140-200) mL.
2. The method for preparing lignin carbon nanodots according to claim 1, characterized in that: In step (1), the water bath heating temperature is 70-90°C and the heating time is 0.5-2h.
3. The method for preparing lignin carbon nanodots according to claim 1, characterized in that: The method also includes the steps of filtering and freeze-drying the blue fluorescent lignin carbon nanodot solution or the red fluorescent lignin carbon nanodot solution to obtain blue fluorescent lignin carbon nanodot powder or red fluorescent lignin carbon nanodot powder respectively.
4. The lignin carbon nanodots prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The lignin carbon nanodots are blue fluorescent lignin carbon nanodots or red fluorescent lignin carbon nanodots.
5. A carbon nanodot composite indium zinc sulfide photocatalyst, characterized in that: The red fluorescent lignin carbon nanodots described in claim 4 are added during the hydrothermal synthesis preparation process of indium zinc sulfide ZnIn2S4, thereby obtaining a carbon nanodot composite indium zinc sulfide photocatalyst, namely, CDs-ZIS photocatalyst.
6. The use of the carbon nanodot composite indium zinc sulfide photocatalyst according to claim 5 in removing pollutants from antibiotic wastewater, characterized in that: By adding CDs-ZIS photocatalyst into antibiotic-contaminated water, pollutants in the water are degraded under light reaction; wherein the pollutants in the antibiotic wastewater are one or more of tetracycline hydrochloride, oxytetracycline, doxycycline, and ciprofloxacin.